A possible S‐glutathionylation of specific proteins by glyoxalase II: An in vitro and in silico study. (December 2016) - Ercolani, Luisa; Scirè, Andrea; Galeazzi, Roberta; Massaccesi, Luca; Cianfruglia, Laura; Amici, Adolfo; Piva, Francesco; Urbanelli, Lorena; Emiliani, Carla; Principato, Giovanni; Armeni, Tatiana
Abstract : Glyoxalase II, the second of 2 enzymes in the glyoxalase system, is a hydroxyacylglutathione hydrolase that catalyses the hydrolysis of S‐d ‐lactoylglutathione to formd‐ lactic acid and glutathione, which is released from the active site. The tripeptide glutathione is the major sulfhydryl antioxidant and has been shown to control several functions, including S‐glutathionylation of proteins. S‐Glutathionylation is a way for the cells to store reduced glutathione during oxidative stress, or to protect protein thiol groups from irreversible oxidation, and few enzymes involved in protein S‐glutathionylation have been found to date. In this work, the enzyme glyoxalase II and its substrate S‐d ‐lactoylglutathione were incubated with malate dehydrogenase or with actin, resulting in a glutathionylation reaction. Glyoxalase II was also submitted to docking studies. Computational data presented a high propensity of the enzyme to interact with malate dehydrogenase or actin through its catalytic site and further in silico investigation showed a high folding stability of glyoxalase II toward its own reaction product glutathione both protonated and unprotonated. This study suggests that glyoxalase II, through a specific interaction of its catalytic site with target proteins, could be able to perform a rapid and specific protein S‐glutathionylation using its natural substrate S‐d ‐lactoylglutathione. Significance: This article reports for the first time a possible additional role of Glo2 that, after interacting with a target protein, is able to promote S‐glutathionylation using its natural substrate SLG, a glutathione derived compound. In this perspective, Glo2 can play a new important regulatory role inS‐glutathionylation, acquiring further significance in cellular post‐translational modifications of proteins.